KEMAMPUAN MENULIS PARAGRAF DESKRIPSI ANAK AUTISTIK SMA ISLAM TERPADU ABDURRAB PEKANBARU - Fajri, Muhammad; Razak, Abdul; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study is to explain the level of ability to write paragraphs description of autistic students at Abdurrab Integrated Islamic High School Pekanbaru. This study uses a type of quantitative descriptive research that is more qualitative. The collection technique in this study uses test and documentation techniques. The ability to write paragraphs of descriptions of autistic children is measured from (a) content and (b) text form. Based on the results of data analysis, the ability to write paragraphs of descriptions of autistic children in the Integrated Islamic High School of Abdurrab Pekanbaru, it is known that in theme 1 the average value of 53.57 is categorized as lacking. Then for theme 2 with an average value of 42.86 in the less category. Based on the results and discussion, the ability to write paragraphs of descriptions of autistic students in Abdurrab Integrated Islamic High School Pekanbaru are categorized as less.Key Words: writing, paragraph description, autistic